On operators preserving inequalities between polynomials - Mattoo , S.G.; Bhat , Mudassir A.; Kumar , Ravinder (North-Western European Journal of Mathematics, 2022)
In this survey article, we explore operator aspects in extremal properties of Bernstein-type polynomial inequalities. We shall also see that a linear operator which send polynomials to polynomials and have zero-preserving property naturally preserve Bernstein's inequality.